Políticas públicas para a educação do campo no estado de São Paulo: impactos, repercussões, contradições e perspectivas - Lima, Elianeide Nascimento (Universidade Federal de São Carlos, 2014)
This thesis aimed to understand the relationships between State and public policies for Field Education, and how they are implemented in the State of São Paulo in Brazil. To do so, it was made an incursion into the State theories on Marx and Gramsci in order to make a counterpoint to the capitalist model of State, specifically in its neoliberal strand. In addition, it was investigated how Education policies have been established in our country, identifying the appointments in the present neoliberal policies within federal level, and how the State of São Paulo has dealt both with the prescribed education policies of the federal Government, as well as how it has been dealing with education and field education. It was necessary search for official documents and scientific productions about those topics, as well as interviewing educators (teachers, coordinators, municipal secretaries of education, in the State of São Paulo) in order to understand the impact of federal public policies for field education on the field education in the State of São Paulo in Brazil.
Keywords: Políticas públicas; Educação do campo; Estado; State; Public policies in education; Field education; CIENCIAS HUMANAS::EDUCACAO